KEPEMIMPINAN AUTENTIK DAN PERFORMANSI: META ANALISIS - P. Eddy Suhartanto (MANASA, 2012)
This article presents a meta-analysis literature study examing the relationshipbetween authentic leadership and performance. Using the Authentic LeadershipQuestionnaires and Performance either on in role perspective or extra role perspective, the authors accumulated 21 correlations from 15 independent studies. Authentic Leadership (self-awareness, relational transparency, balanced processing, and moral) were related to in role performance as well as extra role performance. Summary analysis supported the hypothesis that the authentic leadership will be related to performance. Although the results provided some contributions to the correlation, it is recommended to enhance future research focussing on specific performances